PERSEPSI MASYARAKAT TERHADAP JASA LAYANAN OJEK ONLINE DI PERUMAHAN CITRA GARDEN KECAMATAN TAMPAN KOTA PEKANBARU - Gusti Marlina; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Currently, one of the businesses favored by the community is the transportation service business by motorbike or what used to be called an online motorcycle taxi. Online motorcycle taxis are motorcycle taxis that use technology by utilizing applications on smartphones that make it easier for service users to call online motorcycle taxi drivers. This is what the authors will raise its phenomenon by exploring the perceptions of the lifestyle lovers of the online motorcycle taxi service, the effectiveness of online motorcycle taxis has been running for about 3 years, whether these services will continue to be in demand by the people of Pekanbaru City or not, considering the many conflicts that have occurred related to the emergence of online motorcycle taxis in this city, as well as what are the factors that make the people of Pekanbaru City interested in this online motorcycle taxi service. The formulation of the problem is what is the profile of online motorcycle taxi service users at Citra Garden Housing and how is the perception of online motorcycle taxi service users at Citra Garden Housing.The Teory used in this research is perception theory, rational choice theory and attitude change theory.This type of research is descriptive-qualitative research. The location of this research is in Citra Garden Housing, Tampan District, Pekanbaru City.Informant retrieval techniques in this study is Snowball sampling is an approach to finding key informants who have a lot of information. The profile Gojek Online motorcycle service user at Citra Garden  Housing is the length of time has lived for more than one year in Citra Garden Housing. Peoples perceptions of online transportation (GOJEK-ONLINE) in the city of pekanbaru are very positive. This is marked by the number users of the application in Citra Garden Housing, district Tampan. Keywords :Perception, Society, Ojek Online.